Programas de contingencia para prevención de riesgos y vulnerabilidad por inundaciones en el área agroindustrial de la ESPAM MFL - Cedeño Martinetti, Uriel Alexander (2017)
The research consisted in designing a contingency program that would contribute to the prevention of risks and vulnerability due to flooding in the agro-industrial area of Polytechnic School of Agriculture of Manabí "Manuel Félix López" (ESPAM MFL). It also included a diagnosis of the current vulnerability of floods. For this, the opinions of the personnel with the longest time in the institution (20 people) on the previously recorded floods were considered. Vulnerable areas were characterized through field observations and tabs and this information was represented on a map through the AutoCAD 2014 program 19.1. Rainfall data were collected during the years 2011-2016 at the ESPAM meteorological station in conjunction with the maximum flows evacuated during the rainy season by the La Esperanza dam. Next, the risk and vulnerability of floods were assessed through matrices established by the Secretariat of Risk Management (SGR, 2016). In 2012, the highest level of precipitation in recent years (372.1 mm) was recorded, resulting in material and economic losses. To this, contributed a maximum flow of evacuation of the local dam with a volume of 4409,57 m3; which aggravated the situation for not having a contingency plan. Finally, plans were developed based on preventive measures of contingency according to the available resources of the area. It is concluded that this Program complies with the corrective measures to cover emergencies and to prevent risks and vulnerability due to floods.